Pengaruh NPL terhadap ROA dengan Mediasi CAR dan BOPO Pada Perbankan Indonesia - Maheswari, Kadek Indah; Sudirman, I Made Surya Negara (E-Jurnal Manajemen, 2014)
Normal 0 false false false EN-US X-NONE X-NONE To implement the function of intermediation, banks which deal with the source risks from one of the main activities that is banking activity funds in the form of credit. Ho and Sounder (1981) in his seminars paper state that banks always define the higher rate of interest from the funds of rate interest to get a positive spread as a premium on the risk and to get a profit . The purpose of this research was to determine the effect of NPL on ROA , CAR and ROA with the mediation of banks in Indonesia. The sampling method used was purposive sampling which resulted in a total sample of 18 banks. By using path analysis results of the research found that NPL as a proxy of credit risk has negative effect of profitability with ROA is a proxy. NPL also has negative effect of CAR which is a proxy of capital adequacy and BOPO which is a proxy of operational efficiency. CAR and BOPO mediated partially from the influence on ROA. The results of the study supports all of hypothesis in this study . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: NPL; CAR; BOPO; ROA